Sikap Siswa terhadap STEM : Hubungannya dengan Hasil Belajar Kognitif dalam Pembelajaran IPA - Puspitasari Putri Pambayun; Noly Shofiyah (Universitas Pendidikan Mandalika, 2023)
This study aims to describe students' attitudes towards STEM, cognitive learning outcomes and the relationship between the two variables. This research was quantitative, type of pre-experiment one group pre-test post-test design. The number of samples in this study was 55 class IX students taken from a total population of 192 students. The research instrument consisted of a questionnaire to measure students' attitudes towards STEM and multiple-choice tests to assess students' cognitive learning outcomes. Data were analyzed using N-Gain and person product moment correlation. The results showed that STEM-based learning improved students' attitudes toward STEM and cognitive learning outcomes in science learning. The average score obtained in the pre-test and post-test showed that students' attitudes towards STEM were most dominant in the technology dimension and the lowest in the mathematics dimension. Meanwhile, cognitive learning outcomes in science learning showed that students could master the concept of biotechnology with the highest score increase in the indicator explaining the basic principles of biotechnology. In addition, this approach proves a significant relationship between students' attitudes towards STEM and cognitive learning outcomes in science learning with an R-value of 0,514.